Strategy for Developing Local Food Business Processed from Cassava in Bukit Sari Village, Martapura District, Ogan Komering Ulu Timur Regency - Umaiyah, Riskanatul; Efrianti, Rini; Sari, Yunita; Romadhon, Julkhaidar (ITScience (Information Technology and Science), 2024)
The agricultural sector has a massive role in the economic growth of a country, especially an agrarian country like Indonesia. One effort to improve the community's economy, reduce poverty, and improve the distribution of community income can be made by developing agroindustry. Cassava has become an agro-industrial commodity. Fresh cassava only lasts for a short time and is priced low. However, if further processing is carried out and managed optimally, cassava can provide more excellent economic value, thereby providing substantial profits for farmers and the community. This research aims to analyze strategies that can be formulated and implemented to develop the local cassava food business in Bukit Sari Village, Martapura District, East Ogan Komering Ulu Regency. The research method used in this research is the survey method. The results of this discussion show that there is an opportunity in the cassava chips business for business actors to develop their business into souvenirs from Bukit Sari Village, Martapura District, East Ogan Komering Ulu Regency and the threat to the cassava chips business is that there are competitors for other snack and fast food products so that these cassava chips are forgotten.